Ekstrak Tanaman Binahong sebagai Pengendali Penyakit Hawar Pelepah Daun Padi - Endah Yulia; Fitri Widiantini (Jurnal Fitopatologi Indonesia, 2018)
Binahong Extract for Controlling Sheath Blight Disease of Rice PaddySheath blight disease, caused by Rhizoctonia solani, is an important disease that can affect rice production. The disease is commonly controlled using synthetic fungicides. This study was aimed to test the potential of binahong plant (Anredera cordifolia) as botanical fungicide to inhibit the growth of R. solani and the development of blight disease on rice seedlings. The research was conducted in 2 stages, i.e. in vitro and rice seedling testing. In vitro test was carried out on PDA medium containing different concentrations of binahong leaf extract (0.125%, 0.25%, 0.5%, 1%, and 2%). Rice seedling testing was completed by soaking rice seeds in five concentrations of binahong leaf extract followed by inoculation of R. solani.  The experiments were arranged in a completely randomized design. The variables observed consist of inhibitory ability of binahong leaf extract, colony morphology of R. solani, and disease incidence. Binahong leaf extract inhibited 35.2% growth of R. solani colonies. Treatment of binahong leaf extract had some effects on mycelium of R. solani; macroscopically the mycelium was shorter, thinner and congregated, whereas microscopically it was smaller, elongated and tended to be colourless compared to control. The treatment of 2% binahong leaf extract on rice seeds decreased the incidence of seedling blight disease with the effectiveness reached 100%. Thus, binahong leaf extract has the potential to suppress sheath blight disease caused by R. solani.